2010
DOI: 10.1093/eurheartj/ehq133
|View full text |Cite
|
Sign up to set email alerts
|

Potent anti-ischaemic effects of statins in chronic stable angina: incremental benefit beyond lipid lowering?

Abstract: AimsThe DoUble-blind Atorvastatin AmLodipine (DUAAL) trial investigated whether atorvastatin decreases ischaemia by a vascular benefit, independent of low-density lipoprotein cholesterol lowering, in patients with coronary artery disease (CAD), both alone and in combination with the traditional anti-anginal therapy, amlodipine.Methods and resultsRandomized, double-blind, parallel-group, multicountry trial (2 weeks run-in and 24 weeks active therapy) comparing three treatments: amlodipine, atorvastatin, and aml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…15 The submission to an invasive test in patients whose high probability of CAD would justify the start of treatment may add an unnecessary risk to the propaedeutic of these patients. Emblematic works, such as that carried out by Patel et al 17 in 2010, point to a rate of 39.2% of negative tests for obstructive coronary disease (lesions lower than 20% of luminal obstruction) in 398,978 patients referred to coronary angiography in 663 hospitals, reinforcing the need for a better diagnostic stratification prior to the indication of invasive examination. 18 Hence, it would be more appropriate to relocate the indication of the procedure to those in whom an intervention is planned, may be it angioplasty or surgery.…”
Section: Review Articlementioning
confidence: 99%
“…15 The submission to an invasive test in patients whose high probability of CAD would justify the start of treatment may add an unnecessary risk to the propaedeutic of these patients. Emblematic works, such as that carried out by Patel et al 17 in 2010, point to a rate of 39.2% of negative tests for obstructive coronary disease (lesions lower than 20% of luminal obstruction) in 398,978 patients referred to coronary angiography in 663 hospitals, reinforcing the need for a better diagnostic stratification prior to the indication of invasive examination. 18 Hence, it would be more appropriate to relocate the indication of the procedure to those in whom an intervention is planned, may be it angioplasty or surgery.…”
Section: Review Articlementioning
confidence: 99%
“…10 Similarly, verapamil, a phenylalkylamine CCB derivative, combined with trandolapril, an ACEI, did not differ from an atenolol along with hydrochlorothiazidebased regimen in hypertensive patients with stable CAD. 7 Different from both drugs, amlodipine, a DHP with potent antianginal properties 51 and well tolerated in severe congestive heart failure, 52 decreased cardiovascular events as compared with both placebo and enalapril, an ACEI 8 (Fig. 2, left panel).…”
Section: Jcm 201663mentioning
confidence: 98%
“…Besides, it has been suggested that statins decrease the ability of R. oryzae to damage endothelial cells [52]. Statins are known to improve vascular endothelial health [55], reduce inflammation, and eliminate prothrombotic [56,57]. Mucormycosis has an affinity for invading blood vessels and cause thrombosis and tissue necrosis [6].…”
Section: Statinsmentioning
confidence: 99%